2016
DOI: 10.1614/ws-d-15-00168.1
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of Malaysian Weedy Rice (Oryza sativa): Diversity, Origin and Implications for Weed Management

Abstract: Weedy rice is one of the most dominant and competitive weed species found throughout rice planting areas worldwide. In Malaysia, a combination of agricultural practices such as direct seeding and shared use of machinery has contributed to the rapid proliferation of weedy rice across paddy fields in recent decades. Here, we report on the morphological characterization of weedy rice populations and inferred origin(s) of different morphotypes present in Peninsular Malaysia. Eight weedy rice morphotypes were disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 12 publications
3
50
0
1
Order By: Relevance
“…Song et al [41] recommended that the modern elite rice cultivar is influential in the genetic evolution of Malaysian weedy rice. The recent morphological study of Malaysian weedy rice also supports the perception that the origin of Malaysian weedy rice was mainly contributed by the wild species of Oryza and the modern-bred elite cultivars [42]. The 99% identity of AHAS gene between the weedy rice S and MR219 in this study represented a close resemblance of Malaysia weedy rice to its local cultivated variety of rice.…”
Section: Discussionsupporting
confidence: 83%
“…Song et al [41] recommended that the modern elite rice cultivar is influential in the genetic evolution of Malaysian weedy rice. The recent morphological study of Malaysian weedy rice also supports the perception that the origin of Malaysian weedy rice was mainly contributed by the wild species of Oryza and the modern-bred elite cultivars [42]. The 99% identity of AHAS gene between the weedy rice S and MR219 in this study represented a close resemblance of Malaysia weedy rice to its local cultivated variety of rice.…”
Section: Discussionsupporting
confidence: 83%
“…Notably, more than three-quarters (77%) of weed accessions in our sample set carry functional Rc alleles, a marked contrast from allelic distributions at the domestication genes sh4 , Bh4 , and An-1 . In a recent morphology based study of a larger sampling of Malaysian weedy rice ( N = 193 accessions), Sudinato et al (2016) observed red or brown pericarp color in a comparable proportion of the samples (68%). This suggests that Rc allelic distribution observed here may be generally representative of Malaysian weed populations.…”
Section: Discussionmentioning
confidence: 84%
“…Moreover, Malaysian weedy rice is highly diverse in morphology and phenology. Molecular (Song et al, 2014) and morphological (Sudianto et al, 2016) studies collectively have claimed that the local conventional indica rice cultivars and wild rice (Oryza rufipogon) populations genetically contributed to the complexity of weedy rice in Malaysia. Therefore, synchronization in flowering period between the weedy and cultivated rice and genetic compatibility are expected to support intermittent gene flow across these Oryza groups.…”
Section: Introductionmentioning
confidence: 99%